2014
DOI: 10.1097/ccm.0000000000000654
|View full text |Cite
|
Sign up to set email alerts
|

Feeding the Critically Ill Patient

Abstract: Current evidence suggests that enteral nutrition, started as soon as possible after acute resuscitative efforts, may serve therapeutic roles beyond providing calories and protein. Although many new studies have further advanced our knowledge in this area, the appropriate level of standardization has not yet been achieved for nutrition therapy, as it has in other areas of critical care. Protocolized nutrition therapy should be modified for each institution based on available expertise, local barriers, and exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
141
1
67

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(210 citation statements)
references
References 81 publications
1
141
1
67
Order By: Relevance
“…44 Although optimal protein intakes for surgery are currently not clearly defined, nonsurgical nutrition guidelines suggest that stressed patients should consume at least 1.2-2.0 g of protein/kg/d. 22 Whey protein and casein are among the best quality proteins overall for muscle synthesis 45 and to stimulate anabolism in patients with advanced cancer. 46 Several studies have identified that consuming 25-35 g of protein in a single meal maximally stimulates muscle protein synthesis.…”
Section: Preoperative Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…44 Although optimal protein intakes for surgery are currently not clearly defined, nonsurgical nutrition guidelines suggest that stressed patients should consume at least 1.2-2.0 g of protein/kg/d. 22 Whey protein and casein are among the best quality proteins overall for muscle synthesis 45 and to stimulate anabolism in patients with advanced cancer. 46 Several studies have identified that consuming 25-35 g of protein in a single meal maximally stimulates muscle protein synthesis.…”
Section: Preoperative Interventionmentioning
confidence: 99%
“…The type of nutrition support delivered in the postoperative setting is primarily determined by the patient's ability to achieve calorie (25-30 kcal/kg/d) and protein (1.5-2 g/kg/d) goals and tolerance of oral intake. 1,21,22,90 A practical approach derived from recent publications 1,21,22,90,94 indicates that patients tolerating 50%-100% of nutrition goals should receive high-protein ONS (2-3× a day) to meet protein needs. In patients consuming <50% via the oral route, EN via tube feeds should be given.…”
Section: Postoperative Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that critically ill patients receiving inadequate energy and protein are presented with poor clinical outcomes such as increased risk of infections, length of mechanical ventilations, morbidities and mortality. 7 Although the definition of underfeeding differs in various studies, but it was generally recognized that 80% of prescribed energy and protein represent adequate feeding. 8 It may be more important to ensure protein adequacy as studies have shown that improvement of clinical outcomes is associated with adequate protein intake, even after adjustment for energy adequacy.…”
Section: Feeding Adequacy Among Critically Ill Patients In the Intensmentioning
confidence: 99%
“…Compare to PN, EN has additional benefits of maintaining gut structural and functional integrity, modulating metabolic response, and attenuating oxidative stress and the inflammatory response while supporting the humoral immune system. 7 Therefore, EN (i.e. tube feeding) acts as the first line nutritional therapy in mechanically ventilated critically ill patients who are unable to maintain volitional intake.…”
Section: Feeding Adequacy Among Critically Ill Patients In the Intensmentioning
confidence: 99%